DIVERSITY AND DISTRIBUTION OF EARTHWORMS IN A SUBTROPICAL FOREST ECOSYSTEM OF MOKOKCHUNG DISTRICT, NAGALAND, INDIA - THYUG, LILONGCHEM; KAKATI, L.N. (The Bioscan, 2018)
A comparative study on diversity and distribution of earthworms along with the various physico-chemical factors influencing their distribution was carried out in three sites i.e. natural reserve forest, plantation area and jhum fallow area of a subtropical hill forest ecosystem located in Mingkong area of Mokokchung district, Nagaland, India. Seven species of earthworms representing the three families Moniligastridae, Octochaetidae and Megascolecidae were recorded during the study period of 2013-15. The earthworm density (individuals) and biomass (weight) in the study sites were found to be maximum during the monsoon season viz., plantation area (195.59±5.36 m-2, 96.23±2.50 gm-2) and fallow land (173.48±4.54 m-2, 138.24±3.34 gm -2) however, in the natural forest ecosystem though the density was highest during monsoon (257.71±4.87 m-2), biomass record was maximum during the pre-monsoon season (239.33±3.43 gm-2). The highest annual density (609.68±11.33 m-2) and biomass (549.87±9.05 gm-2) was recorded in the reserve forest ecosystem. Variation of earthworm density and diversity in all the three study sites were found to be affected by different microclimatic and soil physicochemical factors such as soil moisture content, soil temperature, bulk density and nutrient content viz. organic carbon, and total nitrogen.